“Coils of Sunshine”: Charles Smeaton’s Magnesium-Wire Photography in the Catacombs of Rome, 1866-1867 - Osborne, John (Scientia Canadensis, 2022)
In the mid-nineteenth century photographers were challenged by the absence of light in indoor and underground spaces. One promising solution was the intense light created by the combustion of magnesium, which became commercially available in England in 1864. This article examines the use of magnesium wire by the pioneer Canadian photographer Charles Smeaton, who took the first pictures in the Roman catacombs in the winter of 1866-1867.